Dating Papyri Familiarity, Instinct and Guesswork - Choat, Malcolm (2019)
This article surveys the history of palaeographical dating of papyri, reflecting on its origins as a system, and what lessons this might have for contemporary practice. In examining the beginnings of palaeography as a discipline in the late seventeenth century with the work of scholars such as Jean Mabillon, it highlights the concerns of that period, especially the authenticity of documents. In this context, palaeographical dating was only one (though of course an important component) of a range of tools scholars used to date and authenticate texts. In the same way, contemporary scholars use an array of methods to date the texts they study, including script, language, content, and the physical properties of the ink and its support. This article highlights the importance of understanding the limitations of each of these methods, whether caused by their subjective nature or the current limits of scientific knowledge, and emphasizes one of the key lessons of Mabillon's practice, the broad familiarity with many types of script and manuscript which allow these to be properly contextualized and understood.
Keywords: Jean Mabillon; Pierre Hamon; Palaeography; Authenticity; Dating; Papyri